Penerapan Algoritma Coupled Linear Congurential Generator (CLCG) pada Algoritma Kriptografi One Time Pad (OTP) dalam Proses Mengamankan Pesan - Deny Nugroho Triwibowo; Dony Ariyus (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Message is an idea, feeling, or thought of someone whose contents can be in the form of science, entertainment, information, advice, or propaganda. Nowadays, with the development of very advanced technology, one can exchange messages so easily and quickly without any limitations on distance and time. However, with the ease of exchanging messages there are problems that can occur, one of which is the message you want to send opens opportunities for people who want to steal data and information from the message to use it as a crime and will certainly harm certain parties. Therefore, the technique of securing messages is used by using the OTP algorithm and the CLCG random number generator so that messages sent to the security level can be guaranteed. The results of the merging of the OTP and CLCG algorithms in the encryption and decryption process found random key generator does not occur the same key loop with the same characters adjacent to the message. The use of periodic tables in the encryption process also increases the difficulty of deciphering messages because one plaintext character is replaced by many characters in the ciphertext